2023
DOI: 10.1002/jcph.2309
|View full text |Cite
|
Sign up to set email alerts
|

The New S7B/E14 Q&A Document Provides Additional Opportunities to Replace the Thorough QT Study

Abstract: Since 2015, concentration–QTc (C–QTc) analysis has been used to exclude the possibility that a drug has a concerning effect on the QTc interval. This has enabled the replacement of the designated thorough QT (TQT) study with serial electrocardiograms (ECGs) in routine clinical pharmacology studies, such as the first‐in‐human (FIH) study. The E14 revision has led to an increased proportion of FIH studies with the added objective of QT evaluation, with the intention of replacing the TQT study. With the more rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In patients with COPD on treatment with the highest recommended dose, icenticaftor 300 mg twice daily, mean C max at steady state (C max_ss ) was estimated to be 1640 ng/mL. The high clinical exposure scenario was also considered, as detailed in the recent S7B/E14 Q&A document from 2022, 14 that is, mean C max_ss in patients with COPD with impaired clearance when commonly administered with other COPD drugs that could possibly compete with the biotransformation elimination pathway of icenticaftor and thereby elevating icenticaftor plasma exposure levels. If these patients were treated with icenticaftor (as a victim) 300 mg twice daily, mean C max_ss was estimated to rise by no more than 2-fold (3280 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with COPD on treatment with the highest recommended dose, icenticaftor 300 mg twice daily, mean C max at steady state (C max_ss ) was estimated to be 1640 ng/mL. The high clinical exposure scenario was also considered, as detailed in the recent S7B/E14 Q&A document from 2022, 14 that is, mean C max_ss in patients with COPD with impaired clearance when commonly administered with other COPD drugs that could possibly compete with the biotransformation elimination pathway of icenticaftor and thereby elevating icenticaftor plasma exposure levels. If these patients were treated with icenticaftor (as a victim) 300 mg twice daily, mean C max_ss was estimated to rise by no more than 2-fold (3280 ng/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo metabolism of 14 C icenticaftor in both rats and humans along with the analysis of human plasma from the earlier clinical study identified the most abundant circulating metabolites to be N-glucuronide (CKW231 or M8), O-glucuronide (CKW232 or M9) and IOD568 glucuronide, which is formed by O-demethylation process. None of these metabolites showed pharmacological activity in vitro against the wild-type CFTR channel.…”
mentioning
confidence: 99%
“…In our experiments on hNav1.5 we also noticed strong inhibition by cenobamate of the persistent Na + current in the cells where it was detectable, but in the lack of a speci c activator like anemone sea toxin ATX-II we could not quantify this effect. Such effects on multiple human cardiac ion channels could represent an argument for the adequacy of the mechanistic in vitro approach of the CiPA paradigm [10,19,20], which is currently only an optional method under the recently adopted S7B/E14 Q&A cardiac safety testing guidelines, and is still often limited to in vitro hERG screening [23].…”
Section: Discussionmentioning
confidence: 99%